Navigating The Challenges Of Congenital Anomalies Of Recurrent Preauricular Abscesses In Pediatrics: Case Report - Pasaribu, Sitanni O.; Tenty, Tenty (Universitas Pahlawan Tuanku Tambusai, 2024)
Preauricular abscesses, particularly in pediatric patients, are a clinical challenge often associated with congenital anomalies like preauricular pits. These conditions necessitate a comprehensive approach to diagnosis and management, emphasizing the importance of understanding their etiology, clinical presentation, and treatment strategies. A 15-month-old male presented with recurrent preauricular abscesses. Notably, he had congenital preauricular pits present since birth. The clinical presentation included localized swelling, erythema, and tenderness in the preauricular area. The history of recurrent infections and physical examination findings led to the diagnosis of preauricular abscess secondary to infected preauricular pits. The management of preauricular abscesses in pediatric patients involves a dual approach. Initially, appropriate antibiotic therapy is administered to address the acute infection. In cases of recurrence, as in our patient, surgical intervention for the removal of the pit or fistula is considered to prevent future infections. This case highlights the importance of recognizing congenital anomalies and tailoring treatment plans to address both immediate and long-term concerns. This case underscores the need for meticulous clinical assessment and a comprehensive treatment plan in managing pediatric preauricular abscesses. Recognizing the role of congenital preauricular pits in recurrent infections is crucial for effective management. The dual approach of medical and surgical intervention can significantly improve outcomes in pediatric patients with this condition.